CHARACTERISATION OF PYRO OIL FROM TYRE PYROLYSIS FOR ENERGY CONTENT - Akinola, Adebisi; Olaiya, Niyi; Owolabi, Opeyemi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
Disused tyres present formidable problems in terms of disposal and reprocessing, as they are almost immune to biological degradation. Also, the indiscriminate discarding and stockpiling of disused tyres is a challenge to safety and environment. Pyrolysis of scrap tyre to obtain pyrolysis by-products such as pyro-gas, pyrolytic oil and solid residue for useful purpose is a way of ameliorating these problems. In this report, characterisation of liquid product (pyro oil) from the pyrolysis of disused tyres was carried out. Shredded samples of the tyre (in 1 kg batches) were pyrolysed in a refurbished 17.4 litre capacity fixed-bed batch thermochemical reactor at varying temperatures of 250oC, 350oC, 450oC and 600oC with four batched per temperature respectively, and the percentage yield of oil was calculated. Proximate and ultimate analyses of the raw tyre sample and the oil resulting from the pyrolysis were carried out for the determination of the volatile composition, fixed carbon, moisture content and ash content. Fuel properties (heating value, density, kinematic viscosity and flash point) of the oil resulting from pyrolysis were determined, and compared with those of conventional diesel. Finding of the study showed that the pyro oil has a higher heating value than the raw sample, and close to that of conventional diesel, suggesting it as a viable choice of alternative fuel for energy production.